Emerging Biomarkers for Prediabetes : A Review - Dinda Aprilia; Eva Decroli; Alexander Kam; Putri Deas Hadilofyani (Scientific Journal, 2025)
Prediabetes is a global health concern marked by elevated blood glucose levels that do not yet meet the threshold for type 2 diabetes mellitus (T2DM). It is often underdiagnosed despite being associated with insulin resistance, beta-cell dysfunction, and increased cardiovascular risk. Improved strategies for early detection are crucial to prevent disease progression. This review aims to explore novel biomarkers associated with prediabetes and evaluate their potential clinical applications in early diagnosis and risk stratification. A literature search was conducted on English and Indonesian language publications, including original research, case reports, and expert guidelines, focusing on emerging molecular and metabolic biomarkers related to prediabetes. Several promising biomarkers have been identified, including adiponectin, microRNAs, fetuin A, alpha-hydroxybutyrate (α-HB), and Protein Z. Adiponectin demonstrates an inverse relationship with insulin resistance. Specific microRNAs, such as miR-192 and miR-193b, are implicated in glucose metabolism and beta-cell function. Elevated fetuin A levels are linked to hepatic insulin resistance, while increased α-HB levels reflect early metabolic shifts in glucose utilization. Additionally, altered Protein Z concentrations may contribute to prothrombotic states in individuals with prediabetes. In conclusion, these biomarkers offer valuable insight into the pathophysiology of prediabetes and hold potential for enhancing early detection and prevention strategies. However, further validation through large-scale studies is needed before their integration into clinical practice